Q- Switched Nd:YAG Laser Annealing of Phosphorus Diffused Silicon Photodiodes - Ismail, Raid A.; Hamoudi, Walid K.; Abdul Baqi, Shaima’ M. (Iraqi Journal of Laser, 2003)
Improvement of optoelectrical characteristics of phosphorus diffused silicon photodiodes by Q-switched Nd:YAG laser pulses was investigated. Laser pulses have dissolved the precipitation of phosphorus resulted during thermal diffusion process. The experimental data show that responsivity higher than (0.32 A/W) at 850 nm can be achieved after laser annealing with (1.5 MW/cm2) for 6 shots.